#Instacomparison: Social Comparison and Envy as Correlates of Exposure to Instagram and Cyberbullying Perpetration. Issue 3 (June 2023) - Villanueva-Moya, Laura; Herrera, M. Carmen; Sánchez-Hernández, M. Dolores; Expósito, Francisca
Instagram is a popular social networking site (SNS) among adolescents that allows them to share visual content about their lives quickly and easily, increasing social connection, acceptation, and entertainment among others. Nevertheless, SNS exposure can also lead to negative counterparts such as judgments, envy, social comparison, or cyberbullying perpetration. This research aimed to analyze the possible psychosocial factors associated with Instagram use (i.e., social comparison and envy) that could lead to the perpetration of cyberbullying towards peers. The sample consisted of 254 adolescent students aged between 15 and 18 years old ( M age = 15.77, SD = 0.74). The results indicated that high connection time to Instagram, high levels of social comparison, and malicious envy were associated with an increased tendency to carry out cyberbullying perpetration's behaviors. Likewise, the main finding showed that a high connection time to Instagram was associated with increased social comparison, which in turn was associated with malicious envy, and consequently with an increased tendency to carry out cyberbullying perpetration's behaviors. These findings contribute to a better understanding of the psychosocial processes that might precede to perpetrate cyberbullying's behaviors, as well as to promote the development of educational programs intend to encourage the responsible use of SNSs during adolescence.